International bibliography on cropping systems, 1973-1974 - Ramos, Mila M.; Buenviaje, Rufo Q.; Gomez, Arturo (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1976)
The bibliography brings together under one cover the world's scattered literature on cropping systems. It aims to facilitate the literature search and to minimize duplication of efforts of scientists engaged in studies on cropping systems. Following a classified arrangement, the bibliography includes all types of published and unpublished works dealing with all aspects of the subject, which were produced in 1973 and 1974. The compilation, however, is limited to cropping systems involving food crops. Author and keyword indexes are provided to facilitate access to the literature.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Cropping systems -- Bibliography